KEPEMIMPINAN VISIONER KEPALA MADRASAH DI ERA DIGITAL - Elvi Rahmi; Moh. Muslim; Yusnia Binti Kholifah (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2022)
ABSTRACT. This scientific article uses library research. Data is collected through text review and relevant research results. then the data were examined qualitatively by using content analysis. based on the results of the analysis and interpretation of the data, conclusions are drawn which are complemented by suggestions. Besides that, a literature study was carried out by examining various scientific journals and reading books that have a relationship with the visionary leadership of madrasa heads in the digital era. Visionary leadership emphasizes the importance of vision for the organization in realizing an effective and competitive organization. The power of leadership results in various policies and operationalization of work that are guided by the vision of the organization. A visionary leader is highly required to have clear goals and vision in the Institution he leads so that it becomes an advanced and competitive Institution. Thus, a visionary leader must be able to meet the progress that can be realized with full optimism even though there are many obstacles and obstacles. Effective Islamic education leadership can create many indications of achievement in Islamic education institutions, even at the same time the willingness of leaders who make changes and reforms using effective leadership patterns triggers reforms in a better direction. Keywords: Visionary Leadership, Madrasa Head, Digital Era.